[(18)F]-fluoro-ethyl-l-tyrosine PET: a valuable diagnostic tool in neuro-oncology, but not all that glitters is glioma - Hutterer, Markus (Oxford University Press, 2013)
BACKGROUND: To assess the sensitivity and specificity of [(18)F]-fluoro-ethyl-l-tyrosine ((18)F-FET) PET in brain tumors and various non-neoplastic neurologic diseases. METHODS: We retrospectively evaluated (18)F-FET PET scans from 393 patients grouped into 6 disease categories according to histology (n = 299) or distinct MRI findings (n = 94) (low-grade/high-grade glial/nonglial brain tumors, inflammatory lesions, and other lesions). (18)F-FET PET was visually assessed as positive or negative. Maximum lesion-to-brain ratios (LBRs) were calculated and compared with MRI contrast enhancement (CE), which was graded visually on a 3-point scale (no/moderate/intense). RESULTS: Sensitivity and specificity for the detection of brain tumor were 87% and 68%, respectively. Significant differences in LBRs were detected between high-grade brain tumors (LBR, 2.04 ± 0.72) and low-grade brain tumors (LBR, 1.52 ± 0.70; P < .001), as well as among inflammatory (LBR, 1.66 ± 0.33; P = .056) and other brain lesions (LBR, 1.10 ± 0.37; P < .001). Gliomas (n = 236) showed (18)F-FET uptake in 80% of World Health Organization (WHO) grade I, 79% of grade II, 92% of grade III, and 100% of grade IV tumors. Low-grade oligodendrogliomas, WHO grade II, had significantly higher (18)F-FET uptakes than astrocytomas grades II and III (P = .018 and P = .015, respectively). (18)F-FET uptake showed a strong association with CE on MRI (P < .001) and was also positive in 52% of 157 nonglial brain tumors and nonneoplastic brain lesions. CONCLUSIONS: (18)F-FET PET has a high sensitivity for the detection of high-grade brain tumors. Its specificity, however, is limited by passive tracer influx through a disrupted blood–brain barrier and (18)F-FET uptake in nonneoplastic brain lesions. Gliomas show specific tracer uptake in the absence of CE on MRI, which most likely reflects biologically active tumor.